Peningkatan Pemecahan Masalah Dan Kreativitas Belajar Matematika Melalui Pendekatan Scientific Dengan Model Discovery Learning Pada Siswa Kelas VII Semester Genap SMP Negeri 1 Pati Tahun 2014/2015 - Anggraini, Dewi Setya; , Drs. Slamet HW, M.Pd (2015)
The goal of this research is to increase problem solving and creativity to learn math through a scientific approach by applying a model discovery learning to students of VII G class SMP N 1 Pati. The kind of research is a classroom action research conducted in collaboration between teacher and researcher. The students of VII G grade as recipients subject while teachers as a subject of action giver action. Data collection techniques used ware the observation, test, documentation, and field notes. Data analysis techniques used is the data reduction, data presentation, and verification. The result of this research is to increase the ability of problem solving and creativity in learning mathematic that can be seen from the indicators of : 1) understanding the problem, before action 10 students (28,57%), after action 29 students (85,29%); 2) devising a plan, before action 10 students (28,57%), after action 28 students (82,35%); 3) carrying out the plan, before action 7 students (20%), after action 28 students (82,35%); 4) looking back, before action 7 students (20%), after action 27 students (79,41%); 5) fluency, before action 5 students (14,3%), after 29 students (85,29%); 6) flexibility, before action 7 students (20%), after action 25 students (73,53%). Based on the above description can be concluded that the application of the scientific approach to discovery learning model can increase the ability to learn mathematics problem solving creativity